2007
DOI: 10.1515/cclm.2007.136
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 gene polymorphisms in angiographically assessed coronary artery disease: evidence for gender interaction among Brazilians

Abstract: This report shows that the 55LeuLeu PON1 genotype increases CAD risk among female Caucasian-Brazilians, irrespective of other CAD risk factors. In addition, 192GlnGln PON1 homozygotes show higher triglyceride and lower HDL-cholesterol levels in male Caucasian-Brazilians. No associations were detected among African-Brazilians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
(27 reference statements)
1
12
0
3
Order By: Relevance
“…We concluded that gender and PON1 L55M polymorphism interactions vary. Our results are in agreement with the study by Rios et al (37), which showed that PON1 55LL genotype increases CAD risk among female Caucasian-Brazilians, irrespective of other CAD risk factors. We cannot precisely explain the gender effect of PON1 on CAD development, but hormonal differences, diet, lifestyle factors, and other metabolism differences between genders may elucidate our results.…”
Section: Discussionsupporting
confidence: 94%
“…We concluded that gender and PON1 L55M polymorphism interactions vary. Our results are in agreement with the study by Rios et al (37), which showed that PON1 55LL genotype increases CAD risk among female Caucasian-Brazilians, irrespective of other CAD risk factors. We cannot precisely explain the gender effect of PON1 on CAD development, but hormonal differences, diet, lifestyle factors, and other metabolism differences between genders may elucidate our results.…”
Section: Discussionsupporting
confidence: 94%
“…The human PON1 gene is located on chromosome 7 (7q21.3). Several SNPs in PON1 have been associated with HDL-C levels, most notably, two nonsynonymous SNPs, rs662 and rs3202100, which are in strong LD, but results are inconsistent across studies (Table 1) (Blatter Garin et al, 2006;Hegele et al, 1995;Manresa et al, 2006;Rios et al, 2007;van Aalst-Cohen et al, 2005).…”
Section: Genetic Variation In Enzymes Involved In Lipid Metabolism Anmentioning
confidence: 99%
“…Estudos indicaram que o alelo 55L parece ser mais frequente quando comparado ao alelo M, (Brophy et al, 2001;Wang et al, 2003;Santos et al, 2005;Rios et al, 2007;Sepahvand et al, 2007).…”
Section: Pon1 E Hdlunclassified
“…Os níveis da enzima voltam a diminuir com o envelhecimento, possivelmente devido ao desenvolvimento de condições relacionadas ao estresse oxidativo (Seres et al, 2004;Lescai et al, 2009). A atividade e expressão da PON também se diferem entre os sexos, reafirmando a existência de uma relação sexodependente justificada por fatores hormonais (Rios et al, 2007;Costa et al, 2005). As mulheres apresentam níveis de atividade PON significativamente maiores quando comparadas às médias da mesma atividade nos homens (Faggioni, 2003;Costa et al, 2005;Sumegova et al, 2006).…”
Section: Pon1 E Hdlunclassified
See 1 more Smart Citation